Dual-Band Proximity Coupled Feed Microstrip Patch Antenna with ‘T’ Slot on the Radiating Patch and ‘Dumbbell’ Shaped Defected Ground Structure - Dawit Fitsum; Dilip Mali; Mohammed Ismail (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
This paper presents Dual-Band proximity coupled feed rectangular Microstrip patch antenna with slots on the radiating patch and Defected Ground Structure. Initially a simple proximity coupled feed rectangular Microstrip patch antenna resonating at 2.4 GHz is designed. Etching out a ‘Dumbbell’ shaped defect from the ground plane and ‘T’ shaped slot from the radiating patch of the proximity coupled feed rectangular Microstrip patch antenna, results in a Dual-Band operation, i.e., resonating at 2.4 GHz and 4.5 GHz; with 30.3 % and 18.8% reduction in the overall area of the patch and the ground plane of the reference antenna respectively. The proposed antenna resonates in S-band at frequency of 2.4 GHz with bandwidth of 123.6 MHz and C-band at frequency of 4.5 GHz with bandwidth of 200 MHz, and a very good return loss of -22.1818 dB and -19.0839 dB at resonant frequency of 2.4 GHz and 4.5 GHz respectively is obtained. The proposed antenna is useful for different wireless applications in the S-band and C-band.